Kolaborasi Pemerintah Dan Komunitas Lokal Dalam Pencapaian SDGs di Tanoker Ledokombo Kabupaten Jember - Mutiara Novelina; Ria Angin (JURNAL PARADIGMA MADANI : Ilmu Sosial, Politik dan Agama, 2026)
This study is motivated by the importance of collaboration between the government and local communities in supporting the achievement of the Sustainable Development Goals (SDGs), particularly SDG 8 on decent work and economic growth. This study aims to describe the form of collaboration between the Sumber Lesung Village Government and the Tanoker Ledokombo community, as  well as to identify the supporting and inhibiting factors. The method used is a descriptive qualitative approach, with data collection techniques including interviews, observations, and documentation. Data analysis was conducted using the analysis qualitative and tested through triangulation. The results show that the collaboration is implemented through programs such as socialization, skills training, and MSME empowerment, which have an impact on improving skills, job opportunities, and community income. Supporting factors include the support of the village government and community participation, while the obstacles include limited time for participation and lack of communication. In conclusion, collaboration between the government and local communities is able to support participatory and sustainable development and improve the welfare of rural communities.